Le bon endroit. Trouver des lieux pour la cocréation de logements temporaires à prix modéré grâce au projet pilote Solidary Mobile Housing - Aurelie De Smet; Burak Pak; Yves Schoonjans; Geraldine Bruyneel (Brussels Studies, 2023)
In recent years, many cities have begun experimenting with the temporary use of “waiting spaces” as a tool for upgrading the city. A variety of temporary initiatives have emerged. Some civil society organisations see this as an opportunity to address the pressing demand for more and higher quality affordable housing. But how does this work in practice? This paper describes and evaluates the location-finding process developed for the Solidary Mobile Housing Pilot Project, part of an ongoing participatory action research project for the co-creation of temporary housing on urban waiting spaces with and for homeless people. Based on this experience and knowledge exchanges with key experts and field actors, we are assessing the possibilities and limitations of using un(der)used spaces to provide an immediate (although partial and short-term) answer to the current affordable housing crisis through the provision of temporary housing with and for vulnerable people in the Brussels-Capital Region.